An Analysis of Islamic Financial Literacy, Financial Inclusion, and Accounting Information Systems on Financial Performance with Environmental Uncertainty as a Moderator - Dyah Ayumurni Kartikasari; Wita Ramadhanti; M Indra Maulana; Alfarisi Akbar Efendi (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2026)
The aim of this research is to determine the effect of sharia financial literacy, financial inclusion, accounting information systems on financial performance with environmental uncertainty as a moderator. This study uses a quantitative approach with a survey method on 108 respondents. This research is survey research among owners of halal-certified food MSMEs who are members of ASPIKMAS in Banyumas Regency. Based on the results of research and data analysis using SEM (Structural Equation Modeling) it shows that: (1) Sharia financial literacy has a negative effect on financial performance, (2) Financial inclusion has no effect on financial performance, (3) Accounting Information System has a positive effect on financial performance, (4) Environmental uncertainty does not moderate the influence of sharia financial literacy on financial performance, (5) Environmental uncertainty does not moderate the influence of financial inclusion on financial performance, (6) Environmental uncertainty strengthens the influence of accounting information systems on financial performance. The implication of this research is that in an effort to improve the financial performance of MSMEs, business owners should pay attention to knowledge and understanding related to finance, access to financing, and accounting information systems in order to overcome environmental uncertainty that may occur in business. Efforts that can be made are to increase the optimal use of accounting information systems so that they can help business actors in making decisions. Future research is recommended to increase the sample size and examine other variables not explained in this study.